Enhancing Motivation through Work Meaningfulness - Jarred Shellhouse; Hannah S Carter; Matt P Benge (EDIS, 2019)
Proper human resources management can strengthen an organization through strategic talent recruitment and adequate benfits, but employee motivation is also needed to limit absenteeism and ensure an organization is reaching its fullest potential. Research shows various methods that an organizational leader can take to motivate employees by connecting them closer to the meaning of their work. Using a case from former president John F. Kennedy and his relationship to NASA, this article illustrates one way work meaningfulness can be adapted to improve employee motivation for Extension agents.